2011
DOI: 10.1111/j.1472-8206.2011.00950.x
|View full text |Cite
|
Sign up to set email alerts
|

Which psychoactive prescription drugs are illegally obtained and through which ways of acquisition? About OPPIDUM survey

Abstract: The objective of the study was to determine which psychoactive prescription drugs are illegally obtained and through which ways of acquisition. OPPIDUM is an annual national study. It is based on specialized care centers that included subjects presenting a drug dependency or under opiate maintenance treatment. All their psychoactive substances consumed are reported. This work focuses on the different ways of acquisition specially the illegal ways of acquisition (bought on the street, forged prescription, stole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 51 publications
1
34
0
1
Order By: Relevance
“…However, this phenomenon should be contextualized in the global reality of opioids use and abuse, that have large diffusion in the society through different ways of sale. Previous studies suggested poor percentages of Web use in the opioids purchase (1-6%) and a greater confidence of people in local pharmacies than in Internet-based pharmacies (Frauger et al, 2012;Giacometti et al, 2013). The current scenario demonstrates that the application of the new ways of communication could have positive effects on health (de Waure et al, 2012), but it is important to monitor and control the use of these instruments, such as the Internet, in order to avoid some negative effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this phenomenon should be contextualized in the global reality of opioids use and abuse, that have large diffusion in the society through different ways of sale. Previous studies suggested poor percentages of Web use in the opioids purchase (1-6%) and a greater confidence of people in local pharmacies than in Internet-based pharmacies (Frauger et al, 2012;Giacometti et al, 2013). The current scenario demonstrates that the application of the new ways of communication could have positive effects on health (de Waure et al, 2012), but it is important to monitor and control the use of these instruments, such as the Internet, in order to avoid some negative effects.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, 11% were illegally obtained. The different illegal acquisition ways reported were ''street market'' (77.6%), ''gift'' (16.6%), ''theft'' (2.3%), ''forged prescription'' (2.3%), and ''Internet'' (0.7%) (Frauger et al, 2012). These results confirm other available data which report that the role of Internet in the drugs commerce may be overstated (Giacometti et al, 2013;Inciardi et al, 2009;McCabe et al, 2007).…”
Section: Europementioning
confidence: 99%
“…Indeed, in 2008, a French study reported that in 5.9% of cases, methadone was obtained illegally. [30] Finally, methadone dispensing to patients followed in addiction care centres, and those who were hospitalized or incarcerated, are not included in the study database. Because of these limitations, our evaluation underestimates the number of switches and the number of concurrent issues of the two forms.…”
Section: Discussionmentioning
confidence: 99%
“…By making it easier for people to get the medicines without any control, these traders facilitate to feed the habits of people afected by the abuse condition [118][119][120][121].…”
Section: Promotion Of Abuse and Misuse Of Medicinesmentioning
confidence: 99%